Histological Changes in Kidney and Spleen of Albino Mice Treated with Brake Pad Particles - Al-Easawi, Nada Abdulrahman F.; Ghaidan, Hajer Qais; Salman, Shahad Mansour (Iraqi Journal of Science, 2019)
In this study, the consequences of treatment with brake pad particles on kidney and spleen were evaluatedthrough microscopic anatomy sections for 60 male albino mice. The animals were divided into six groups, the first three groups (A,B,C) were exposed to brake pad particles depending on periods of exposure (4, 8, and 12weeks, respectively), while the other three groups were control groups,designated asF, which were exposed to laboratory fresh air only. A special locally-designed inhalation chamber was used to expose the animals. The exposure dose to brake pad particles (total suspended particles) was 2.228 Âµg/mÂ³ for 30 min/day, 5 days/week,4, 8 and 12 weeks.The statistical analysis showed that the weights of organs for both kidney and spleen of treated mice had highly significant differences (P< 0.01) compared with control groups.The histological sections examination of the kidney, when compared with the control group, showed subcapsular tubular vascular degeneration and mild cortical focal hemorrhage in group A that was exposedto brake pads particlesfor 4 weeks. In group B, the exposure for 8 weeks resulted in cortical vascular degeneration, cortico-medullary vascular congestion, focal interstitial nephritis, and thickening of interstitial tissue.Other effects included marked dilation of collecting ducts with tubular vascular degeneration, necrosis, glomerular degeneration and deterioration, and cast formation. Group C, exposed for 12 weeks , showed similar changes of the kidney to those of group B. As related to spleen sections,they demonstrated mild subcapsular vascular degeneration of lymphocytes in group A,while the exposure in group Bresulted in moderate amyloid deposits with hemosiderosis, along withmild subcapsular vascular degeneration of lymphocyteswithin the red pulp. In group C, which was treated for 12 months, severe splenomegaly with advanced secondary splenic amyloidosis was also observed within the red pulp.It was characterized by marked deposited acellular and amorphous pinkish homogenous material within red pulp.The continuous exposure to brake pad particles causes harmful effectson the tissues ofessential body organs in human health.These particles should be thought-about as a sort of additional air pollutants in several cities of Iraqin the future.